The nitrogen removal characterization and ecological risk assessment of Bacillus sp. isolated from mariculture systems in China with spatiotemporal difference. - Qian Zhang; Yingeng Wang; Zheng Zhang; Yongxiang Yu; Chunyuan Wang; Meijie Liao; Xiaojun Rong; Zhiqi Zhang; Bin Li; Jianlong Ge; Jinjin Wang (PLoS ONE)
The accumulation of nitrogen compounds may worsen the aquatic environment and cause serious economic losses in the aquaculture industry. In this study, the denitrification performance and ecological safety of 120 Bacillus sp. isolates with spatial and temporal differences were evaluated based on the aspects of hemolysis, drug resistance, denitrification performance, and purification effect for mariculture wastewater. Firstly, 55/120 safe strains with no hemolytic activity were detected through hemolysis testing. Then, based on selective denitrification medium and colorimetric reagent method, 34/55 Bacillus sp. with denitrification effect were screened. For these 34 Bacillus sp. isolates, the drug resistance phenotype and genotype, denitrification genes, and enzyme activities related to the nitrogen metabolizing (AMO, HAO, NAR, NIR) were examined. And the MARI was 0.00-0.25, with a multi-drug resistance rate of 17.6%. The drug resistance genes tetB, blaTEM, and cfr and the denitrification genes nap, nor, and narG were detected. Ultimately, 27/34 strains with denitrification function and ecological safety were obtained. In addition, eight Bacillus sp. showed certain denitrification effects on nitrogen-containing wastewater treatment. Among them, B. subtilis B24 has outstanding denitrification ability, with removal rates of 92%, 62%, 68%, and 30% for NH4 + -N, NO2--N, NO3--N, and TN in simulated wastewater, respectively. It also has a good denitrification effect in practical applications. This study provides candidate bacterial strains for the treatment of mariculture wastewater.